Meningkatkan Keterampilan Berhitung Operasi Penjumlahan Bilangan Asli Menggunakan Media Manik-Manik Pada Siswa Kelas I SDN N0. 14 Inpres Cikowang Kabupaten Takalar - Nurdesiana Nurdesiana; Sukmawati Sukmawati; Rezki Ramdani (Jurnal Bintang Pendidikan Indonesia, 2024)
This research aims to improve the calculation skills for the operation of adding natural numbers using beads as a medium for class I students at SDN No. 14 Cikowang Presidential Instruction, Takalar Regency. The type of research used is Class Action Research which consists of two cycles where each cycle is carried out in three meetings. Research procedures include planning, action, observation and reflection. The subjects in this research were class I students at SDN No. 14 Cikowang Presidential Instruction, Takalar Regency as many as 23 people. The research instruments used in this research were observation sheets and giving learning outcomes tests. The data collection techniques used are observation and tests. The results of the research showed that in cycle I, of the 23 students who completed individually, only 13 students or 57% met the minimum completion criteria (KKM) or were in the very low category. Classically it has not been fulfilled because the average value obtained was 63.1%. Meanwhile, in cycle II, of the 23 students, 23 had fulfilled the KKM and the average score obtained by students was 93.2%, which was in the very good category. Based on the results of the research above, it can be concluded that the use of bead media can improve the numeracy skills of adding natural numbers in class I students at SDN No. 14 Cikowang Presidential Instruction, Takalar Regency.